2019
DOI: 10.1007/s40820-019-0263-3
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Synthesis of Fluorescent Mesoporous Silica–Carbon Dot Nanohybrids Featuring Folate Receptor-Overexpressing Cancer Cell Targeting and Drug Delivery

Abstract: HIGHLIGHTS• A one-pot method was developed for the preparation of fluorescent mesoporous silica nanoparticles-carbon dots (MSNs-CDs) nanohybrid.• The MSNs-CDs nanohybrid showed stable and bright yellow emission, excellent biocompatibility, and specific targeting capability toward folate receptor-overexpressing cancer cells and can be applied as fluorescence imaging-guided drug carriers for effectively delivering anticancer drugs to tumor sites.ABSTRACT Multifunctional nanocarrier-based theranostics is supposed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(48 citation statements)
references
References 63 publications
0
45
0
Order By: Relevance
“…The heat generated by laser light by the complexes easily damage the cells which triggered the release of DOX from complexes. Prasad et al [162,163] used mesoporous silica nanoparticles as a carrier. DOX and CDs were loaded into the mesoporous silica nanoparticles and conjugated FA on the surface of nanoparticles.…”
Section: Theragnostic Agent Based On Cdsmentioning
confidence: 99%
“…The heat generated by laser light by the complexes easily damage the cells which triggered the release of DOX from complexes. Prasad et al [162,163] used mesoporous silica nanoparticles as a carrier. DOX and CDs were loaded into the mesoporous silica nanoparticles and conjugated FA on the surface of nanoparticles.…”
Section: Theragnostic Agent Based On Cdsmentioning
confidence: 99%
“…In mostly 80–90% of epithelial ovarian cancers, other gynecological cancers, lung cancers and breast cancers, the FRα is highly overexpressed and gaining increasing importance to be exploited for targeted cancer therapy [ 81 ]. Considering this fact, several research groups have reported the enhanced specific cellular uptake of MSN in various cancer cells, having overexpressed folate receptors by modifying MSN surface with folic acid [ 82 , 83 , 84 , 85 , 86 ]. Nonetheless, using two different human pancreatic cancer xenografts on different mouse species, Lu et al have also shown dramatic improvements in tumor-suppression effect by using folic acid functionalized camptothecin-loaded MSN in comparison with unfunctionalized MSN [ 87 ].…”
Section: Surface Modification Of Msn For Passive and Active Targetmentioning
confidence: 99%
“…Functionalized QD-embedded MSN with high quantum yield have been largely exploited for selective tumor imaging in vivo, as well as for cancer cell imaging and detection in vitro by the intracellular internalization of QDs [ 278 , 279 ]. Recently, Zhao et al have reported the synthesis of fluorescent Carbon Dot-MSN nanohybrids [ 86 ]. Nevertheless, Cheng et al have reported tri-functionalized MSN, effectively decorated to be used in the field of theranostics coordinating the trio of target, imaging, and therapy in a discrete entity [ 280 ].…”
Section: Msn As Cancer Theranosticsmentioning
confidence: 99%
“…The results indicated that SONH has higher drug loading ability where about 97% of the drug is released in a lower pH over 7 days in contrast to 20% release at neutral pH. In addition, multifunctional fluorescent mesoporous amine functionalized SONH decorated with folate receptors (MSN–CDs) has been developed to allow image guided delivery of DOX into folate receptor overexpressing HeLa cells (S. Zhao et al, ). Codelivery of drugs with small interfering RNA (siRNA), targeting the pump P‐gp can overcome issues pertaining to MDR.…”
Section: Different Types Of Oinhsmentioning
confidence: 99%